2016
DOI: 10.1002/jbm.b.33738
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fatigue on the corrosion resistance of common medical alloys

Abstract: The effect of mechanical fatigue on the corrosion resistance of medical devices has been a concern for devices that experience significant fatigue during their lifespan and devices made from metallic alloys. The Food and Drug Administration had recommended in some instances for corrosion testing to be performed on post-fatigued devices [Non-clinical tests and recommended labeling for intravascular stents and associated delivery systems: guidance for industry and FDA staff. 2005: Food and Drug Administration, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…After undergoing fretting testing, p ‐values were obtained to statistically compare rest, breakdown, and over potential values between pairs of as received, soak, small, and large fretted samples composed of the same alloy as shown in Table . As observed in a previous study, comparisons between MP35N as received and soak samples yielded significantly different results for the rest potential ( p = 0.002). Half of the comparisons between the as received/soak and fretted MP35N samples resulted in significantly different rest potential values with all the soak vs large fretted MP35N comparisons showing statistical significance ( p < 0.001).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…After undergoing fretting testing, p ‐values were obtained to statistically compare rest, breakdown, and over potential values between pairs of as received, soak, small, and large fretted samples composed of the same alloy as shown in Table . As observed in a previous study, comparisons between MP35N as received and soak samples yielded significantly different results for the rest potential ( p = 0.002). Half of the comparisons between the as received/soak and fretted MP35N samples resulted in significantly different rest potential values with all the soak vs large fretted MP35N comparisons showing statistical significance ( p < 0.001).…”
Section: Resultssupporting
confidence: 88%
“…Cardiovascular devices constructed of metallic alloys can undergo fretting and fatiguing conditions in vivo , both of which could damage the protective oxide layer on their surfaces and potentially lead to pitting corrosion. In a previous study performed in our laboratory, fatigue conditions alone were shown to not significantly affect the pitting corrosion susceptibility of metallic alloys commonly implanted in vivo . The work herein set out to determine the effect that wire fretting alone has on the pitting corrosion susceptibility of several metallic alloys commonly used to manufacture intravascular stents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrosion susceptibility as measured by ASTM F2129 was generally unaffected by the NaClO soak in our tests. Regardless of NaClO condition, EP nitinol had higher breakdown potentials than BO nitinol similar to other studies (Ref 16, 22). The NaClO soak led to a statistically significant decrease in rest potential for the BO nitinol although the absolute change in average E r was within the range of expected variability for the test as described in ASTM F2129.…”
Section: Discussionsupporting
confidence: 91%